# Class 9 RD Sharma Solutions – Chapter 6 Factorisation of Polynomials- Exercise 6.4 | Set 1

**In each of the following, use factor theorem to find whether polynomial g(x) is a factor of polynomial f(x), or not(Question 1-7):**

### Question 1. f(x) = x^{3 }– 6x^{2 }+ 11x – 6, g(x) = x – 3

**Solution: **

Given:f(x) = x^{3 }– 6x^{2 }+ 11x – 6, g(x) = x – 3Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.Here,

x – 3 = 0

x = 3

To prove:g(x) is a factor of f(x), that is f(3) = 0On substituting the value of x in f(x), we get

f(3) = 3

^{3 }– 6 × 3^{2 }+ 11 × 3 – 6= 27 – (6 × 9) + 33 – 6

= 27 – 54 + 33 – 6

= 60 – 60

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 2. f(x) = 3x^{4 }+ 17x^{3 }+ 9x^{2 }– 7x – 10, g(x) = x + 5

**Solution: **

Given:f(x) = 3x^{4 }+ 17x^{3 }+ 9x^{2 }– 7x – 10, g(x) = x + 5Here,

x + 5 = 0

x = -5

To prove: g(x) is a factor of f(x), that is f(-5) = 0On substituting the value of x in f(x), we get

f(-5) = 3(-5)

^{4}+ 17(-5)^{3}+ 9(-5)^{2}– 7(-5) – 10= 3 × 625 + 17 × (-125) + 9 × 25 + 35 – 10

= 1875 – 2125 + 225 + 35 – 10

= 2135 – 2135

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 3. f(x) = x^{5 }+ 3x^{4 }– x^{3 }– 3x^{2 }+ 5x + 15, g(x) = x + 3

**Solution: **

Given:f(x) = x^{5 }+ 3x^{4 }– x^{3 }– 3x^{2 }+ 5x + 15, g(x) = x + 3Here,

x + 3 = 0

x = -3

To prove:g(x) is a factor of f(x), that is f(-3) = 0On substituting the value of x in f(x), we get

f(-3) = (-3)

^{5 }+ 3(-3)^{4 }– (-3)^{3 }– 3(-3)^{2 }+ 5(-3) + 15= -243 + 243 + 27 – 27 – 15 + 15

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 4. f(x) = x^{3 }– 6x^{2 }– 19x + 84, g(x) = x – 7

**Solution: **

Given:f(x) = x^{3 }– 6x^{2 }– 19x + 84, g(x) = x – 7Here,

x – 7 = 0

x = 7

To prove:g(x) is a factor of f(x), that is f(7) = 0On substituting the value of x in f(x), we get

f(7) = 7

^{3 }– 6 × 7^{2 }– 19 × 7 + 84= 343 – (6 × 49) – (19 × 7) + 84

= 343 – 294 – 133 + 84

= 427 – 427

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 5. f(x) = 3x^{3 }+ x^{2 }– 20x + 12, g(x) = 3x – 2

**Solution: **

Given:f(x) = 3x^{3 }+ x^{2 }– 20x + 12, g(x) = 3x – 2Here,

3x – 2 = 0

x = 2/3

To prove:g(x) is a factor of f(x), that is f(2/3) = 0On substituting the value of x in f(x), we get

Taking L.C.M

=

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 6. f(x) = 2x^{3 }– 9x^{2 }+ x + 13, g(x) = 3 – 2x

**Solution: **

Given:f(x) = 2x^{3 }– 9x^{2 }+ x + 13, g(x) = 3 – 2xHere,

3 – 2x = 0

x = 3/2

To prove:g(x) is a factor of f(x), that is f(3/2) = 0On substituting the value of x in f(x), we get

= 0

Since, the result is 0,

Hence, proved that g(x) is a factor of f(x).

### Question 7. f(x) = x^{3 }– 6x^{2 }+ 11x – 6, g(x) = x^{2 }– 3x + 2

**Solution: **

Given:f(x) = x^{3 }– 6x^{2 }+ 11x – 6, g(x) = x^{2 }– 3x + 2Here,

x

^{2 }– 3x + 2 = 0On factorizing the above, we get

⇒ x

^{2}– 3x + 2 = 0⇒ x

^{2 }– 2x – x + 2 = 0⇒ x(x – 2) – 1(x – 2)

⇒ (x – 1)(x – 2) are the factors

To prove:g(x) is a factor of f(x), that is f(1) and f(2) should be 0Let x = 1

On substituting the value of x in f(x), we get

f(1) = 1

^{3 }– 6 × 1^{2 }+ 11 × 1 – 6= 1 – 6 + 11 – 6

= 12 – 12

= 0

Let x = 2

On substituting the value of x in f(x), we get

f(x) = 2

^{3 }– 6 × 2^{2 }+ 11 × 2 – 6= 8 – (6 × 4) + 22 – 6

= 8 – 24 +22 – 6

= 30 – 30

= 0

Since, the results are 0 g(x) is the factor of f(x)

### Question 8. Show that (x – 2), (x + 3) and (x – 4) are the factors of x^{3 }– 3x^{2 }– 10x + 24

**Solution: **

Given:f(x) = x

^{3 }– 3x^{2 }– 10x + 24Factors given are (x – 2), (x + 3) and (x – 4)

To prove:g(x) is a factor of f(x), that is f(2), f(-3), f(4) should be 0Here, x – 2 = 0

Let, x = 2

On substituting the value of x in f(x), we get

f(2) = 2

^{3 }– 3 × 2^{2 }– 10 × 2 + 24= 8 – (3 × 4) – 20 + 24

= 8 – 12 – 20 + 24

= 32 – 32

= 0

Here, x + 3 = 0

Let, x = -3

On substituting the value of x in f(x), we get

f(-3) = (-3)

^{3 }– 3 × (-3)^{2 }– 10 × (-3) + 24= -27 -3(9) + 30 + 24

= -27- 27 + 30 + 24

= 54 – 54

= 0

Here, x – 4 = 0

Let, x = 4

On substituting the value of x in f(x), we get

f(4) = (4)

^{3 }– 3 × (4)^{2 }– 10 × (4) + 24= 64 – 3(16) – 40 + 24

= 64 – 48 – 40 + 24

= 84 – 84

= 0

Since, the results are 0, g(x) is the factor of f(x)

### Question 9. Show that (x + 4), (x – 3) and (x – 7) are the factors of x^{3 }– 6x^{2 }– 19x + 84

**Solution: **

Given:f(x) = x

^{3 }– 6x^{2}– 19x + 84Factors given are (x + 4), (x – 3) and (x – 7)

To prove:g(x) is a factor of f(x), that is f(4), f(3), f(-7) should be 0Here, x + 4 = 0

Let, x = -4

On substituting the value of x in f(x), we get

f(-4) = (-4)

^{3 }– 6(-4)^{2 }– 19(-4) + 84= -64 – (6 × 16) – 19 × (-4) + 84

= -64 – 96 + 76 + 84

= 160 – 160

= 0

Here, x – 3 = 0

Let, x = 3

On substituting the value of x in f(x), we get

f(3) = (3)

^{3 }– 6(3)^{2 }– 19(3) + 84= 27 – 6(9) – 19 × 3 + 84

= 27 – 54 – 57 + 84

= 111 – 111

= 0

Here, x – 7 = 0

Let, x = 7

On substituting the value of x in f(x), we get

f(7) = (7)

^{3 }– 6(7)^{2 }– 19(7) + 84= 343 – 6(49) – 19 × 7 + 84

= 343 – 294 – 133 + 84

= 427 – 427

= 0

Since, the results are 0, g(x) is the factor of f(x)

### Question 10. For what value of a is (x – 5) a factor of x^{3 }– 3x^{2 }+ ax – 10

**Solution: **

Here, f(x) = x

^{3 }– 3x^{2 }+ ax – 10By factor theorem

If (x – 5) is the factor of f(x) then, f(5) = 0

⇒ x – 5 = 0

⇒ x = 5

On substituting the value of x in f(x), we get

f(5) = 5

^{3 }– 3 × 5^{2 }+ a × 5 – 10= 125 – (3 × 25) + 5a -10

= 125 – 75 + 5a – 10

= 5a + 40

Equate f(5) to zero

f(5) = 0

⇒ 5a + 40 = 0

⇒ 5a = -40

⇒ a = -40/5

⇒ a = -8

When a = -8, then (x – 5) will be factor of f(x)

### Question 11. Find the value of such that (x – 4) is a factor of 5x^{3 }– 7x^{2 }– ax – 28

**Solution: **

Given:f(x) = 5x^{3}– 7x^{2}– ax – 28Using factor theorem

(x – 4) is the factor of f(x), then f(4) = 0

⇒ x – 4 = 0

⇒ x = 4

On substituting the value of x in f(x), we get

f(4) = 5(4)

^{3 }– 7(4)^{2 }– a × 4 – 28= 5(64) – 7(16) – 4a – 28

= 320 – 112 – 4a – 28

= 180 – 4a

Equate f(4) to zero, to find a

f(4) = 0

⇒ 180 – 4a = 0

⇒ a = 180/4

⇒ a = 45

When a = 45, then (x – 4) will be factor of f(x)

### Question 12. Find the value of a, if (x + 2) is a factor of 4x^{4 }+ 2x^{3 }– 3x^{2 }+ 8x + 5a

**Solution: **

Given:f(x) = 4x^{4}+ 2x^{3}– 3x^{2}+ 8x + 5aUsing factor theorem

If (x + 2) is the factor of f(x), then f(-2) should be zero

⇒ x + 2 =0

⇒ x = -2

On substituting the value of x in f(x), we get

f(-2) = 4(-2)

^{4}+ 2(-2)^{3}– 3(-2)^{2}+ 8(-2) + 5a= 4(16) + 2 (-8) – 3(4) – 16 + 5a

= 64 – 16 – 12 -16 + 5a

= 5a + 20

Equate f(-2) to 0

f(-2) = 4(-2)

^{2}+ 2(-2)^{3}– 3(-2)^{2}+ 8(-2) + 5a= 4(16) + 2(-8) – 3(4) – 16 + 5a

= 64 – 16 – 12 – 16 + 5a

= 5a + 20

Equate f(-2) to 0

f(-2) = 0

⇒ 5a + 20 = 0

⇒ 5a = – 20

⇒ a = -4

When a = -4, then (x + 2) is the factor of f(x)